Technical report writing in engineering studies - Mohd Raus, Teh Zanariah; Yusoff, Marianna; Balakrishnan, Subatira (Universiti Teknologi Malaysia, 2019)
Technical reports are very important in engineering domain, as they are the main genre in reporting and communicating information among members in an engineering community. In addition, the engineering students need to be competent in writing technical report because an effective technical report will determine them in being hired and being promoted in their future career. A set of questionnaires was distributed to sixty undergraduates from the Faculty of Electronics and Computer Engineering, Universiti Teknikal Malaysia Melaka (UTeM) to seek the engineering students’ knowledge on technical report writing. Additionally, samples of students’ technical report writing were analysed by using the Genre Analysis approach for technical report writing (Cheung & Lai, 1997) to identify the Move Structure involved in writing technical report. The findings indicated that the students have already obtained the knowledge of generic structure in report genre and five Move Structure were identified in technical report writing. This study has recommended the ESP practitioners to use the genre-based approach in teaching technical report writing to the students as it allows them to have better understanding on how the technical reports were structured and organised.